Comparação entre os critérios da NBR 15812-1:2010 e NBR 15961:2011 com os do projeto de norma da NBR 16868-1:2020 - Rizzatti, Lorenzo Sartori (2020)
As is known, there are currently two regulations in force in Brazil that dictate the design of structural masonry, differently from European and American normative codes which use only one standard. Separated by the type of material of the structural block, there is the standard for ceramic blocks and the one that addresses concrete blocks. Thus, the new Standard NBR 16868:2020 – Part 1: Project, which is currently in the process of national consultation, aims to unify the regulations in force in the country, so that there is a single standard that addresses the design of structural masonry. This work has as main objective to comparatively analyze the normative criteria of ABNT NBR 15812 – 1 (2010) Structural masonry - Ceramic blocks Part 1: Projects and ABNT NBR 15961 – 1 (2011) Structural masonry – Concrete blocks Part 1: Projects, with the proposals of the Standard Project of NBR 16868:2020 – Part 1: Project, in order to contribute and subsidize, through examples, the discussions with the technical environment. The requirements, properties of the masonry and its components, safety and limit states, actions, design values, structural analysis, displacements, cracks and dimensioning were analyzed. It was concluded that the standard design of NBR 16868: 2020 enters public consultation in good time, due to the long period without updates to the standards and their criteria. Effective and positive changes were introduced for the design of structural masonry, but without the maintenance of some specific criteria, which would fit alterations, in addition to communication failures between the regulations and the reader.